Pengaruh Rebusan Daun Kelor terhadap Produksi ASI Ibu Nifas di Desa Pilar Jaya Tahun 2022 - Siti Hajar; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Aulia Ariyani (PPNI UNIMMAN, 2024)
One of the plants that is believed to help increase breast milk production is the Moringa leaf (Moringa oleifera). This plant is known as the